2017
DOI: 10.1111/exd.13304
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cell markers CD1a and CD207 are the most rapidly responding genes in lesional psoriatic skin following adalimumab treatment

Abstract: TNFα-, IL-23- and IL-17-targeting drugs are highly effective in the treatment of psoriasis. However, the precise molecular mechanism remains unknown. In psoriatic skin, the presence of Langerhans cells (LCs) is reduced, but the role of LC is poorly understood. The purpose of this study was to investigate the impact of TNFα and IL-23/IL-17 on the presence of LC in the skin during treatment. Therefore, psoriatic skin was investigated before and after 4 days of adalimumab or ustekinumab treatment. Furthermore, TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
2
12
0
1
Order By: Relevance
“…These authors demonstrate that Langerin + cells can enhance DMBA-induced DNA damage, although in light of recent findings, it remains to be established whether the LCs are the main Langerin + DCs that are capable of metabolizing DMBA. Indeed, various reports now show that the DMBA-metabolizing activity of LCs is dispensable for inflicting H-Ras mutations in keratinocytes ( 120 , 121 ).…”
Section: Lcs In Cancermentioning
confidence: 99%
“…These authors demonstrate that Langerin + cells can enhance DMBA-induced DNA damage, although in light of recent findings, it remains to be established whether the LCs are the main Langerin + DCs that are capable of metabolizing DMBA. Indeed, various reports now show that the DMBA-metabolizing activity of LCs is dispensable for inflicting H-Ras mutations in keratinocytes ( 120 , 121 ).…”
Section: Lcs In Cancermentioning
confidence: 99%
“…Reduced migration of LCs toward inflammatory cytokines is attributed to the IL-17-induced keratinocyte secretome ( 77 ). A possible consequence of this migrational impairment is the accumulation of LCs in the dermis ( 67 , 78 82 ), where they form dermal aggregates with T cells outside lymphatic vessels (Figures 2 A–C). The localization of LCs in dermis and basal epidermis, adjacent to the basement membrane in areas where dermal immune cells are entering the epidermis, raises questions on the nature of interactions between LCs and other inflammatory cells, questions that at large remain to be answered.…”
Section: Altered Localization Of Lcs Within Psoriasis Lesionmentioning
confidence: 99%
“…5 The expression of the genes that code for CD1a and CD207 are downregulated early in successful treatment of psoriasis with adalimumab. 6 Studies in the imiquimod mouse model of psoriasis have suggested that dendritic cells including Langerhans cells are essential for the development of psoriasis-like inflammation. 7 The study by Eaton et al in this issue of the BJD builds on previous work from this group.…”
mentioning
confidence: 99%